Stadium for Foundation Organisations Athletic Association - http://id.worldcat.org/fast/175028 (1920)
Item is an architectural drawing by Samuel Maclure prepared for Foundation Organisations Athletic Association of Victoria, B.C.; Plans, elevation and sections. Bleachers and grandstands for Victoria Stadium, a baseball field in the block bounded by Douglas, Humboldt and Belleville Streets.; Douglas Street between Humboldt and Belleville Streets, Victoria, B.C.